Impact of dietary and lifestyle choices on menstrual patterns in medical students - U., Sreelakshmi; Tushara Bindu, V.; T., Subhashini; Saritha, K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of the study was to evaluate average age of menarche, the pattern and types of menstrual disorders and their relation with BMI, dietary habits, physical exercise and stress. Methods: A cross sectional prospective study was conducted on female medical students during the academic year 2018-2019 at Mallareddy medical college for women, Suraram, Hyderabad, India. The various life style factors including BMI, junk food consumption and physical exercise were factored. Prevalence of each different menstrual abnormality were identified and analyzed by Chi-squire test and p value <0.005 was considered as statistically significant. Results: Study included 255 medical students who had attained menarche without known medical problems. Mean age of menarche was 12.81years. The most frequent menstrual disorders were premenstrual syndrome 192 (75 %), dysmenorrhoea 146 (57 %), and irregular cycle 97(38%). Statistically significant association of Body mass index (BMI) related to premenstrual syndrome (PMS) and dysmenorrhoea was reported (both p<0.05). Similarly, statistically significant association of lack of physical activity had greater risk of premenstrual syndrome and dysmenorrhoea (both p<0.0001). Unhealthy dietary patterns had statistically significant higher risk for dysmenorrhoea (p<0.0001). Conclusions: In conclusion premenstrual symptoms, dysmenorrhoea and menstrual irregularities were more prevalent. Majority of symptoms were stress, pain abdomen, irritability, mood swings. Comprehensive education programs on lifestyle modifications like regular physical activities, promoting healthy eating habits should be emphasised to prevent menstrual abnormalities of young students as early as at school level.